Prospects Of Using Public Relations Technology In The Activities Of Political Parties - Meyliyeva Gulnoza Minggirovna (Genius Journals, 2024)
Before analyzing public relations for political parties in modern Uzbekistan, it is necessary to briefly focus on the universal concepts of political science, namely, the concepts of civil society, the rule of law, political parties and socio-political movements. Public relations – PR – is known worldwide as an important element of business relations
Keywords: government; politics; democracy; society